Proteomic characteristics of plasma and blood cells in natural aging rhesus monkeys. Issue 21 (13th October 2022) - Wu, Na; Xiao, Fuchuan; Zhang, Jing; Chi, Yafei; Zhai, Yanan; Chen, Baian; Lu, Jing
Abstract: Aging has become a serious social issue that places a heavy burden on society. However, the underlying mechanisms of aging remain unclear. This study sought to understand the aging process as it may be affected by proteins in the blood, the most important functional system for material transportation in the body. We analyzed and compared the protein expression spectrums in the blood of old and young rhesus monkeys and found 257 proteins expressed differentially in plasma and 1183 proteins expressed differentially in blood cells. Through bioinformatics analysis, we found that the differentially‐expressed proteins in plasma were involved in signal pathways related to complement and coagulation cascades, pertussis, malaria, phagosome, and cholesterol metabolism, while the differentially‐expressed proteins in blood cells were involved in endocytosis, proteasome, ribosome, protein processing in the endoplasmic reticulum, and Parkinson's disease. We confirmed that the protein levels of complement C2 in plasma and actin‐related protein 2/3 complex subunit 2 (ARPC2) in blood cells obviously decreased, whereas the complement C3 and complement component 4 binding protein beta (C4BPB) significantly increased in plasma of old rhesus monkeys and C57BL/6 mice. Our results suggest that C2, C3, C4BPB, and ARPC2 can be used as target proteins for anti‐aging research.